Pengaruh Pembelajaran Jarak Jauh terhadap Self-Concept dan Self-Efficacy Siswa - Nurphadila Nurphadila; Syamsiah Nur; Sri Mulyati; Seri Yanti Siagian (Al-Liqo: Jurnal Pendidikan Islam, 2021)
The purpose of the study was to obtain information about the effect of distance learning on students' self-concept and self-efficacy in Islamic Religious subjects at the junior high schools in Tembilahan District, Indragiri Hilir Regency. This research was field research by a mixed-method approach. The informants and sample in this study were 60 students and three teachers. The data collection techniques using interviews, questionnaires and analyzed using validity test, and hypothesis testing. The results showed there was an effect of distance learning on students' self-concept by R square 0.083. There was an effect of distance learning on students' self-concept and self-efficacy in hypothesis 1 by R Square of 0.083, while hypothesis 2 scored R Square of 0.175.